Analisis Strategi Pengembangan Usaha Kompos pada BUMDes Karya Bersama di Desa Delima Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Putri, Melia Eka; H, Afriani; Sulaksana, Indra (Universitas Batanghari Jambi, 2025)
This study aims to formulate an appropriate development strategy to strengthen the position of the compost business in supporting the village economy sustainably. The research method uses a descriptive approach, with data collection through observation and interviews with BUMDes administrators. Data were analyzed using the IE matrix, SWOT, and QSPM to obtain the appropriate strategy. The results show the position of BUMDes in the IE matrix in cell I, which recommends a grow and build strategy. The main strategies formulated include increasing human resource capacity through training, optimal utilization of local raw materials, developing a wider marketing network, and compost product innovation to increase competitiveness in the market. In conclusion, BUMDes Karya Bersama has great potential to develop a sustainable compost business through intensive and integrative strategies.